Managing Cultural Heritage of Ancient Settlement of Kisipidi through Urban Design - Shrestha, Bijaya K; C., Mamta G. (Administration and Management Review, 2011)
The cultural heritage of Kisipidi, a satellite newari settlement of Kathmandu constitutes the physical setting and socio-religious activities, which is linked by cultural practice in the form of daily ritual, celebration of various festivals, community’s social norms including traditional social institution ‘guthi’ system. Though the town had been sustained for the last many centuries, failure to continue such practice in socioeconomic modernisation at present has resulted in formation of incompatible built form, decaying of community spaces, reduction in socialisation and religious activities and increase in environmental pollution. All these emerging problems are in the first stage of destruction. However, they can not be addressed through the existing legal and institutional framework due to its inadequacy and ineffectiveness. In such situation, integration of both ‘top down’ approach and ‘bottom up’ strategy by formulating conservation oriented development plan (and program) at town level and reviving socio-cultural activities at local level through urban design techniques is essential. Keywords: Cultural heritages; Socio-religious activities; Urban design; Kisipidi Administration and Management Review Volume 22, No. 1, January, 2010 Page: 88-102 Uploaded Date: 2 December, 2011